Role of hysteroscopy and transvaginal sonography and its correlation with histopathological examination in perimenopausal abnormal uterine bleeding - Bawankar, Ruchita; Singh, Neetu; Paliwal, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abnormal uterine bleeding is any abnormal uterine bleeding outside normal volume, duration, regularity or frequency. Transvaginal sonography allows detailed assessment of anatomical abnormalities of the uterus and endometrium pathologies of the myometrium. Visual assessment can be done by hysteroscopy and cellular assessment by histopathology. Methods: This descriptive prospective cross-sectional study was conducted in Rama medical college hospital & research centre, Kanpur. 103 Perimenopausal women of 40-45 years of age with AUB attending gynecology OPD of RMCH were included. Particulars of woman regarding menstrual history, obstetric history were asked for. Systemic examination, gynaecological examination and Specific investigations like TVS, Hysteroscopy were also done. Results: The mean ET by TVS for endometrial hyperplasia >15.59±6.22mm, uterine leiomyomas >13.5±2.12 mm, normal endometrium >7.57±3.28 mm and polyp >10.17±3.55 mm. The endometrium- normal on TVS 73 women (70.88%) followed by endometrial hyperplasia 22 women (21.36%), Uterine polyp 6 (5.82%) and Uterine leiomyoma 2 women (1.94%). Conclusions: Causes of AUB- hormonal imbalance, endometrial polyp, endometrial hyperplasia, and leiomyomas were other causes of AUB in perimenopausal women. Hysteroscopy can detect endometrial pathology with varying accuracy which was better than TVS in detecting endometrial pathology. In the present study more than 50% women had normal findings on TVS and hysteroscopy.